In vitro, greenhouse, and field assessment of cassava lines for resistance to anthracnose disease caused by colletotrichum gloeosporiodes f. sp. Manihotis - Fokunang, C.N.; Dixon, Alfred G.O.; Ikotun, T.; Asiedu, Robert; Tembe-Fokunang, E.A.; Akem, C.N. (2002)
Fifty-three cassava lines were selected from breeding populations at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria and screened in vitro for resistance to cassava anthracnose disease (CAD). The in vitro inoculation of stem cuttings with the fungus Colletotrichum gloeosporioides f.sp. manihotis showed significant differences (p ± 0.05) in acervuli production and in the sensitivity of the cassava lines to the fungal infection after 7 days of incubation at 25 ◦C. Cassava lines 88/01084, 91/00595, 91/00475, 91/00344, 91/00684, 91/00313, 91/00422, and 91/00344 were highly resistant, with necrotic lesion sizes less than 7 mm. In contrast pedigree lines 88/02549, 89/0008, 91/00390 and 91/00402 were highly susceptible with the largest necrotic lesion size being greater than 20 mm. Ten cassava lines from the in vitro screening that showed varying levels of resistance to CAD were selected, based on their flowering abilities for diallel hydridization trials, and were further screened in greenhouse and field trials for CAD resistance. The greenhouse and field screening showed significant varietal differences (p ± 0.05) in sensitivity to the fungus. In all cases, the progeny lines showed correlated levels of resistance irrespective of the type of screening or assessments. Correlation analysis of the in vitro, greenhouse and field assessments showed that there was a good correspondence among all three methods of evaluating for CAD